Long-Tailed Macaques (Macaca fascicularis) and Humans Interactions in Grojogan Sewu Natural Park (TWA GS), Karanganyar Regency, Central Java Province - Moh. Jafron Syah (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2020)
Macaca fascicularis is one species of primate that easily adapts to various habitats, such as disturbances habitat, like a natural park. The conflict between M. fascicularis and human increases due to changes in ecology. In Borneo, Sumatra, Malaysia, Mauritus, and Thailand, M. fascicularis has become pests because destroyed orchards and plantations. Interaction between M. fascicularis and human, which occurred at several natural parks in Singapura and Kaliurang caused by M. fascicularis’s attraction to food brought by humans. This research aimed to study the interaction between M. fascicularis with the humans in Grojogan Sewu Natural Park (TWA GS) by direct observation and also an interview with visitors, workers, and villagers. Based on direct observation, frequency of affiliation interaction between humans and M. fascicularis (55.56%) is higher than agonistic interaction (44.4%). The dominant affiliation interaction was sitting nearby the visitors (42.96%); meanwhile, the most dominant agonistic interaction was stealing (54.12%) because the M. fascicularis attracted to food (67.02%). Workers reported having more nuisance problem with M. fascicularis than visitors and villagers. Almost all of the respondents thought that M. fascicularis needs to be kept alive in the park, and consider conservation and protection of the macaques are essential.